Fetal cardiac morphology and geometry in pregnancies with class A1 and A2 gestational diabetes mellitus. (19th March 2022) - Turgut, Ezgi; Turan, Gökçe; Özdemir, Halis; Aktulum, Fatma; Bayram, Merih; Karcaaltincaba, Deniz
Abstract: Objective: To evaluate whether certain parameters on fetal cardiac morphology and geometry measured at 20–22 weeks of gestation differ in subsequently diagnosed gestational diabetes mellitus (GDM) pregnancies and whether these changes are associated with disease severity as indicated by class A1 and A2 GDM. Method: It was designed as a retrospective study. All measurements were taken between 20 and 22 weeks of gestation. We compared fetal cardiac structural measurements of 200 uncomplicated pregnancies (control group) with those of 307 GDM patients (160 of the them were regulated with diet (GDM A1) and 147 of them received insulin treatment (GDM A2) during pregnancy). GDM were diagnosed between 24-28 weeks of gestation with 75 gram (g) oral glucose tolerance test. Results: The interventricular septum (IVS) was thicker in both in GDM A2 and GDM A1 than control ( p  < .001, p  < .001), and there was statistically significant difference between GDM A2 and GDM A1 ( p  = .012). In both left and right wall thickness in GDM A1 and GDM A2 were remarkably higher than control group ( p  < .001, p  < .001, p  < .001, p  < .001). The left and right spherical indices were higher in both GDM A1 and GDM A2 groups than controls ( p  = .021 and p  = .028). Left and right area in GDM A1 and GDM A2 groups were significantly smaller than control groups ( p  < .001 and p  = .001). Conclusion: Gestational diabetes is a common obstetric morbidity, which causes fetal cardiac structural changes. Our study shows that these changes can occur during the early weeks of pregnancy.